Federal Republic of Yugoslavia : 2002 Article IV Consultation, Third Review Under the Stand-By Arrangement, and Request for an Extended Arrangement-Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Federal Republic of Yugoslavia. (IMF Staff Country Reports; Country Report ;, 2002)
This paper assesses the Federal Republic of Yugoslavia's (FRY) 2002 Article IV Consultation, Third Review Under the Stand-By Arrangement (SBA), and a Request for an Extended Arrangement. Despite the impressive achievements since late 2000, when FRY succeeded to membership in the IMF, the challenges facing the authorities remain daunting. The FRY authorities' medium-term program of stabilization sets a good basis for achieving sustainable growth and a viable external position, and deserves the continued support of the IMF through completion of the third review under the current SBA and approval of the proposed extended arrangement.